Uncertainty concerning the 4-field box technique for Stage-IB2 carcinoma of the uterine cervix - Thakur, Priyanka (Medknow Publications & Media Pvt Ltd, 2013)
Radiation Therapy (RT) plays a pivotal role in the curative approach for carcinoma of the cervix. Inspite of the emergence of various new conformal techniques in RT, conventional techniques still hold vital importance. Majority of the patients worldwide are treated with 2D-RT techniques. 2D-RT techniques have been proven to be non-inferior and simpler in comparison to 3D-RT in the context of carcinoma of the cervix. However, inadequate target volume coverage with improper portal design can preclude the chances of cure. We demonstrate the need for abolishing guesswork in terms of target volume determination through the example of a patient's sagittal magnetic resonance image showing a case of the retroverted uterus which would have been likely to be missed from the treatment portals if they were designed using definitions based on bony landmarks.